(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In understanding an image, extraction of characters existing in the image is considered to be important. Scene images are different from document images, which are composed of characters and complicated background i.e. photo, picture, or painting etc. instead of white one that makes it difficult to be dealt with. Extraction and localization of scene text are used in many applications. In this paper, we have proposed a connected component based method to extract text from natural images. The proposed method uses colour space processing. Character recognition is done through OCR that accepts the input in form of text boxes, which are generated through text detection and localization stages. The Proposed method is robust with respect to font size, colour, orientation, and style. Results of the proposed algorithm, by taking the real scenes, including indoor and outdoor images, shows that proposed method efficiently extracts and localizes the scene text. In this paper, we have introduced a new method to extract characters from scene images using mathematical morphology.Â